Spatial Structure of Road Netwrok and Levels of Settlements Development- A Case Study of Shirahtti Taluk, Gadag District, Karnataka: A Quantitative Approach - Nayak, L. T.; Shyagoti, N. G. (National Geographical Journal of India, 2022)
Not available